ANALYSIS OF FACTORS AFFECTING THE PERFORMANCE OF HEALTH WORKERS AT THE BARONG TONGKOK HEALTH CENTER, WEST KUTAI REGENCY - Depit Manual; Iskandar; Sudirman (Indonesian Journal of Multidisciplinary Science, 2022)
The purpose of this study was to determine the effect of leadership, work motivation, work discipline, training, competence, education, work environment, workload and work stress on the performance of health workers at Barong Tongkok Health Center, West Kutai Regency, either partially or simultaneously. This research is a type of quantitative research using multiple linear regression analysis approach. The population in this study were all 51 health workers with samples taken from the entire population or often called the census method. Data collection methods are primary data and secondary data. The data analysis used is validity test, reliability test, multiple linear regression analysis, t test, F test and coefficient of determination test. The results of the study prove that partially leadership has a significant effect on performance with a significance level of 0.024 < 0.05, work motivation has a significant effect on performance with a significance level of 0.000 < 0.05, work discipline has a significant effect on performance with a significance level of 0.024 < 0.05, training has a significant effect on performance with a significance level of 0.025 < 0.05,  competence has a significant effect on performance with a significance level of 0.027 < 0.05, work environment has a significant effect on performance with a significance level of 0.048 < 0.05, workload has a significant effect on performance with a significance level of 0.023 < 0.05, work stress has a significant effect on performance with a significance level of 0.031 < 0.05,  but education has no significant effect on performance with a significance level of 0.522 > 0.05. Simultaneously Leadership, work motivation, work discipline, training, competence, education, work environment, workload and work stress have a significant effect on the performance of health workers at the Barong Tongkok Health Center, West Kutai Regency with a significance level of 0.000 <0.05.